(untitled) (University Journal of Zoology, Rajshahi University, 2008)
Studies were made on the number of egg clutch, copulating pairs, duration of mating, duration of egg laying, and weight of egg clutch of Pila globosa by inducing it with Pituitary Gland (PG) and Optic Tentacle cut (OT) under laboratory condition. The effect of inducing the animal with PG and OT cut showed that it resulted in an increase in the number of egg clutch in comparison with that of the control. In control animals the number of egg clutch was found to be 0.30±0.02 which was 20.93% of total egg clutches laid. Whereas in animals with Pituitary Gland (PG) and Optic Tentacles (OT) cut the number of egg clutch were 0.43±0.61 and 0.70±0.86 which were 30.23% and 48.83% of total egg clutches laid respectively. The animals injected with pituitary gland extract and optic tentacle cut showed an increase in the number of egg clutch in comparison with that of the control animals. In control animals, duration of mating, duration of egg laying, and weight of egg clutch were found as, 3.23±0.29hrs., 5.37±1.51hrs., and 8.38±g respectively. The pituitary gland (PG) injected and optic tentacle (OT) cut, duration of mating, duration of egg laying and weight of egg clutch were found as, 3.52±0.26hrs., 4.64±1.63hrs., and 8.54±2.10g.; 3.51±0.33hrs., 5.47±1.19hrs., and 8.45±2.53g respectively. Key words: Pila globosa, induced breeding, Commercial Farming. Univ. j. zool. Rajshahi Univ. Vol. 26, 2007. pp. 35-39